2011
DOI: 10.1098/rstb.2010.0226
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial symbionts in insects or the story of communities affecting communities

Abstract: Bacterial symbionts are widespread in insects and other animals. Most of them are predominantly vertically transmitted, along with their hosts' genes, and thus extend the heritable genetic variation present in one species. These passengers have a variety of repercussions on the host's phenotypes: besides the cost imposed on the host for maintaining the symbiont population, they can provide fitness advantages to the host or manipulate the host's reproduction. We argue that insect symbioses are ideal model syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
298
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(309 citation statements)
references
References 114 publications
(147 reference statements)
2
298
0
9
Order By: Relevance
“…Buchnera's association with aphids is ancient, being approximately 200 million years old and revolves around the endosymbiont's capacity to synthesize essential amino acids for its host (van Ham et al, 2003). Due to their pleiotropic effects on their hosts, the situation is not so clear-cut for the non-essential (secondary) endosymbionts, as their transmission may be both vertical and horizontal and the ratio between cost and benefits strictly depends on environmental conditions (Ferrari and Vavre, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buchnera's association with aphids is ancient, being approximately 200 million years old and revolves around the endosymbiont's capacity to synthesize essential amino acids for its host (van Ham et al, 2003). Due to their pleiotropic effects on their hosts, the situation is not so clear-cut for the non-essential (secondary) endosymbionts, as their transmission may be both vertical and horizontal and the ratio between cost and benefits strictly depends on environmental conditions (Ferrari and Vavre, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their obligate biotrophy (Bonfante and Genre, 2010), many of them harbor endobacteria in their cytoplasm (Bonfante and Anca, 2009). Bacterial endosymbionts are widespread among animals (Wernegreen, 2012;McFall-Ngai et al, 2013) and in particular the ones living in insect tissues have been investigated in depth (Ferrari and Vavre, 2011). In contrast, examples of endobacteria living inside the fungal cells are much more limited (Bianciotto et al, 2003;Partida-Martinez and Hertweck, 2005;Lackner et al, 2009;Naumann et al, 2010;Kai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…number of genotypes) increases diversity of associated arthropod communities, confers greater resilience to biotic and abiotic stressors, and affects key aspects of ecosystem function [21,27,28,[31][32][33][34][35]. Recently, studies have begun to extend the scope of community genetics research to examine how genetic variation and population divergence within herbivorous insects, endosymbionts [36][37][38] and predaceous fishes [39][40][41][42] have cascading bottom-up and topdown effects within communities. And finally, a related area of research labelled 'eco-evolutionary dynamics' has shown that evolution within prey populations can influence predator-prey dynamics within microcosms [43 -45].…”
Section: Introductionmentioning
confidence: 99%
“…However, such studies of two-way interactions (e.g. between a plant and its herbivore or an insect herbivore and its symbionts) cannot always predict the responses of organisms in a community [7][8][9]. Here, we adopt a community approach and simultaneously examine the role of both plant -and insect -microbial interactions in modulating the plant -herbivore interaction.…”
Section: Introductionmentioning
confidence: 99%